Multisensor Remote Sensing and Advanced Image Processing for Integrated Assessment of Geological Structure and Environmental Dynamics - Luo Bin; Rana Waqar Aslam; Iram Naz; Dmitry E. Kucher; Zohaib Afzal; Danish Raza; Rana Muhammad Zulqarnain; Yahia Said (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Lake, a crucial freshwater resource in semiarid region, requires comprehensive understanding for sustainable management. This study presents a comprehensive methodological framework that integrates various remote sensing techniques with field investigations to examine the geological structure, environmental conditions, and land use patterns of the lake. Sentinel-2 imagery was utilized alongside spectral indices, such as normalized difference vegetation index (ranging from –0.237728 to 0.604622), normalized difference water index (–0.564981 to 0.297745), and normalized difference moisture index (–0.25 to 0.320), as well as advanced image processing methods, such as principal component analysis (PCA), minimum noise fraction, and structural analysis, to assess and characterize the lake’s environmental features. PCA (first principal component values: –4046.55 to 3813.42) revealed distinct lithological variations, while directional lineament analysis in four orientations [north–south (NS), northwest–southeast (NWSE), east–west, and northeast–southwest] identified predominant structural trends controlling the lake’s morphology. Land use classification achieved high accuracy (overall accuracy: 92%, Kappa coefficient: 0.89) in distinguishing six major classes, with bare ground dominating the landscape and agricultural activities concentrated along the eastern shore. Digital elevation model analysis (–1 to 44 m) and slope assessment (0–37.8114°) demonstrated strong correlations between topography and land use patterns. The integration of these techniques revealed that the lake’s formation and current configuration are strongly influenced by geological structures, particularly evident in NS and NWSE trending features. Our methodology successfully identified critical relationships between geological structure, environmental conditions, and human land use, providing a robust framework for similar studies in semiarid regions. The findings indicate that sustainable management of lake requires the consideration of both structural controls and anthropogenic influences, with particular attention to the eastern shore’s development patterns where human activities are concentrated.